Trade liberalization and economic growth: A study on Ghana, Nigeria and Cote d'Ivoire - Francis Amoasah (FIW - Research Centre International Economics, 2018)
The study considers the relationship between trade liberalization and economic growth among three sub-Saharan African countries: Ghana, Nigeria, and Cote d'Ivoire. We find no statistically significant increase in the economic growth of the countries following trade liberalization. However, post-trade-liberalization exports (and trade) of the countries did increase. Yet, the need for the promotion of exports in high value-added industries remain an age long unduly overdue problem. Increases in imports following liberalization dominate the increases in exports, export earnings remain susceptible to international price volatility and a chunk of the export commodities remain unprocessed as well as broadly narrow in range. The EU, US and China are the major trading partners to Africa, even more (in percentage terms) than the continent trades among itself. While reasonable efforts are being made on the African Continental Free Trade Area (AfCFTA), it should be seen that regional economic integration does not automatically improve growth. However, proper desegregation with the needed checks and balances may help yield for Africa some gains from trade. It is time, therefore, that the countries devise important measures to ensure that these envisaged significant gains from trade are duly realised.
Keywords: F43; O10; C23; O40; 330; trade liberalization; convergence; Sub-Saharan Africa